Brexit and the EU in Global Climate Governance - Dupont, Claire (2019)
Climate change governance is one of the EU’s priorities. The EU has developed a central (and arguably, a leading) role in global climate governance. The UK has been an important supporter of strong climate action both within the EU and in international climate negotiations. We investigate how/whether the EU’s role in global climate governance will be affected by Brexit by focusing on potential changes in three conditions for EU leadership: (1) credible and ambitious internal climate policy; (2) constant and effective international engagement through climate diplomacy; and (3) the ability to attract followers. We find that the UK has sometimes played the role of a pivotal outlier, either pushing for more internal policy ambition or blocking certain policy options. Brexit is likely to have cumulative effects on the EU’s role in global climate governance over the long term, through a series of changes in internal EU policymaking and climate diplomacy. The speed and scope of these changes depend on the nature of the future UK–EU relationship. We argue that the broader international context and strains on EU unity represent more urgent challenges to the EU’s role in global climate governance than those posed by Brexit.